Enhanced piezoelectric properties of electrospun poly(vinylidene fluoride)/multiwalled carbon nanotube composites - Ahn, Yongjin; Im, Joon Young; Seo, Yongsok; Hong, Soon Man (ADAPTIVE, ACTIVE AND MULTIFUNCTIONAL SMART MATERIALS SYSTEMS, 2012)
We prepared poly(vinylidene fluoride)/multiwalled carbon nanotube (MWCNT) nanocomposites using electrospinning process and investigated its effect on the polymorphic behavior and electroactive properties. The remanant polarization and piezoelectric response increased with the the amount of MWCNT and piezoelectric beta-phase crystal. Interfacial interaction between MWCNT and PVDF caused high degree of beta-phase derived from external stretching.